Efficacy of Open Textbook Adoption on Learning Performance and Course Withdrawal Rates: A Meta-Analysis - Virginia Clinton; Shafiq Khan (SAGE Publishing, 2019)
Open textbooks have been developed in response to rising commercial textbook costs and copyright constraints. Numerous studies have been conducted to examine open textbooks with varied findings. The purpose of this study is to meta-analyze the findings of studies of postsecondary students comparing learning performance and course withdrawal rates between open and commercial textbooks. Based on a systematic search of research findings, there were no differences in learning efficacy between open textbooks and commercial textbooks (k = 22, g = 0.01, p = .87, N = 100,012). However, the withdrawal rate for postsecondary courses with open textbooks was significantly lower than that for commercial textbooks (k = 11, OR (odds ratio) = 0.71, p = .005, N = 78,593). No significant moderators were identified. Limitations and future directions for research, such as a need for more work in K-12 education, outside of North America, and that better examine student characteristics, are discussed.